1998
DOI: 10.1159/000026194
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-II Risk Factors in Native Americans in Florida

Abstract: Earlier virologic studies established that human T-cell lymphotropic virus type II (HTLV-II) is the predominant retrovirus type found among Seminole Indians in southern Florida. We studied 46 members of the Seminole tribe living on 3 reservations to determine the risk factors for HTLV-II and to investigate disease association with the virus. The donors’ plasma samples were evaluated with the enzyme-linked immunosorbent and Western blot assays. DNA extracted from their peripheral blood mononuclear cells were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…The fact that there is no evidence for HTLV-II infection among the Iroquois and yet it is quite prevalent among the Seminole raises the question as to whether the Seminole became infected at a later time (perhaps through interactions with South or Central American or Caribbean Indians) after they split from Northeastern Indian groups. This hypothesis is consistent with the observed high degree of homology between HTLV-II sequences detected in Seminole Indians and isolated Indian groups of Central and South America [31,32].…”
Section: Discussionsupporting
confidence: 90%
“…The fact that there is no evidence for HTLV-II infection among the Iroquois and yet it is quite prevalent among the Seminole raises the question as to whether the Seminole became infected at a later time (perhaps through interactions with South or Central American or Caribbean Indians) after they split from Northeastern Indian groups. This hypothesis is consistent with the observed high degree of homology between HTLV-II sequences detected in Seminole Indians and isolated Indian groups of Central and South America [31,32].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence found in the present study is similar to that observed in previous studies involving indigenous populations in the Americas. In Venezuela, the prevalence among the Guahibo [19] was estimated at 24.8%, and among the Seminole Indians in the United States, at 24% [24]. However, lower prevalence rates have been reported in the Yahgans in Chile (9.1%) [26], in the Wayuu in Colombia (4.8%) [35] and in the Wichi-Mataco in Argentina (above 3%) [25].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in blood donors had already demonstrated a rate of HTLV infection of 0.72/1,000 in New Mexico (most cases of which were attributed to HTLV-2) and, in turn, a higher prevalence among American Indian blood donors (1.0%-1.6%) than among non-Hispanic white donors (0.009%-0.06%) 65 . In the United States, HTLV is endemic among the Navajo and Pueblo people of New Mexico and Seminole people of Florida, with HTLV-2 presenting a higher prevalence 85 , 88 ( Table 1 and Fig. 2 ).…”
Section: Htlv In Indigenous Groups Of Other Countries Of the Americasmentioning
confidence: 99%